Analisis Peran Kompetensi, Komitmen Organisasi, dan Employee Engagement terhadap Kinerja Karyawan PDAM Kota Padang - Dewirahmadanirwati, Dewirahmadanirwati; Sababalat, Jurminarti (Lembaga Yasin AlSys, 2025)
The decline in employee performance at PDAM Kota Padang is reflected in high rates of absenteeism, tardiness, and low productivity, indicating a gap in understanding the internal factors influencing performance. This study aims to examine the effects of competence, organizational commitment, and employee engagement on employee performance. A quantitative approach with a survey method was used, involving 95 respondents selected through total sampling. The research instrument was a standardized questionnaire that had been tested for validity and reliability. Data were analyzed using multiple linear regression to assess the partial and simultaneous effects of each variable. The results show that all three variables, competence, organizational commitment, and employee engagement, have a positive and significant effect on employee performance. Among them, employee engagement emerged as the most dominant factor, indicating that employees who are emotionally and cognitively involved in their work demonstrate high dedication and are capable of achieving optimal performance. These findings highlight the importance of human resource management strategies focused on enhancing individual competence, strengthening organizational loyalty, and creating a supportive work environment that fosters psychological engagement. Such strategies are essential for maintaining and improving service quality in public sector organizations like PDAM.